The distribution of genetic polymorphism of CYP3A5, CYP3A4 and ABCB1 in patients subjected to renal transplantation - Vavić Neven; Rančić Nemanja; Cikota-Aleksić Bojana; Magić Zvonko; Cimeša Jelena; Obrenčević Katarina; Radojević Milorad; Mikov Momir; Dragojević-Simić Viktorija (Vojnosanitetski Pregled)
Background/Aim. Polymorphisms of genes which encode transporter P-glycoprotein and most important enzymes for tacrolimus pharmacokinetics can have significant influence reflecting on blood concentrations of this drug. The aim of this study was to examine the distribution of polymorphisms of CYP3A5, CYP3A4 and ABCB1 genes in patients subjected to renal transplantation, for the first time in our transplantation center. Methods. The research was designed as a prospective cross-sectional study which included 211 patients subjected to renal transplantation in the Centre for Solid Organ Transplantation of the university tertiary health care hospital, Military Medical Academy, Belgrade, Serbia. Patients of both genders, 22−69-year-old, Caucasians, subjected to immunosuppressive regimen, including tacrolimus, were recruited for the study. CYP3A5 6986A>G (the *3 or *1, rs776746), CYP3A4 - 392A>G (the *1 or *1B, rs2740574) and ABCB1 3435C>T (rs1045642) genotypes were determined by TaqMan® SNP genotyping assays. Results. Most of our patients (94.8%) had functional CYP3A4 enzyme, while 87.7% of all the patients had diminished CYP3A5 enzymatic activity. On the other hand, about one third of them, 31.3%, had functional ABCB1 transporter. Conclusion. A total of 84.8% of our patients were found to express both the CYP3А5*3*3 genotype (associated with diminished CYP3А5 enzymatic activity) and CYP3А4*1*1/*1*1B (associated with functional CYP3А4 enzymatic activity), while out of all the patients with diminished CYP3A5 enzymatic activity, 68.7% had diminished activity of ABCB1 transporter. However, further studies are necessary in order to show the influence of these genetic polymorphisms on tacrolimus blood concentrations in patients after renal transplantation.